A charter of William the Conqueror and two of his sons - David Bates (Tabularia)
I omitted a document from my edition of the charters of William the Conqueror on the grounds of arguments which had suggested that it was a charter of William Rufus. The signa are not all consistent with the document’s date of 1084, but the charter, which is included in a pancarte destroyed in 1944, should be regarded as a charter of William I to which additions were made soon after his death. The document has some significance for the politics of 1088 and for relations between the Conqueror’s sons.